Implementation of STEM-PBL Design Based Students E-Worksheet to Improve Problem Solving Skills - Suryanti, Suryanti; Natadiwijaya, Ismail Fikri; Nurohman, Sabar (FKIP Universitas Lampung, 2024)
Problem solving skills is an ability that students have to learn in the 21st century. Problem solving skills can be improved through a combination of learning activities including media, models and learning approaches. This study aims to determine the enhancement of students' problem solving skills through the implementation of STEM-PBL based e-worksheet on energy and its change material in grade VIII middle school. This research type is pre-experimental with a one group pretest-postest design. The research sample consisted of one class VIII of SMPN 2 Badau totaling 25 students was determined by random sampling. Data collection using a problem solving skills test instrument with 4 essay questions. Data analysis using descriptive analysis of the data collected. Analysis of feasibility data obtained through validation questionnaire validated by three expert validators meanwhile data on the improvement of problem solving skills obtained through the pre-test and post-test results given to students before and after the implementation of STEM-PBL design based e-worksheets. The results of the validity of the STEM-PBL design e-worksheet from this study were obtained an average assessment score from the three expert validators of 96.9% with very valid criteria so that STEM-PBL design based e-worksheets can be applied to science learning. Problem solving skills indicators that experienced the highest to lowest increase due to the implementation of STEM-PBL design based e-worksheet were understand the problem by 0.83; plan the solution by 0.71; execute the solution by 0.63; and reflect on the problem solving solution by 0.37. The results showed an N-Gain of 0.56 with a medium category. Based on the results of the N-Gain percentage of 56.52%, it can be concluded that the implementation of STEM-PBL design based e-worksheet on energy and its change material is effective enough to increase students' problem solving skills. Keywords: e-worksheet, problem based learning, problem solving skills, STEM-PBL.DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1665-1677